AVALIAÇÃO DA POROSIDADE E CARBONO TOTAL EM ÁREA EXPERIMENTAL DA UEMS MUNICÍPIO DE MUNDO NOVO - MS - CUNHA, Vinícius Estigarribia; OZORIO, Jefferson Matheus Barros; LINGNAU, Bruno Ian; SOUZA, Durval Kauê de Almeida; TOLOTTO, Luiz Felipe Furlanetto; CASTILHO, Selene Cristina de Pierri (ANAIS DO ENIC, 2025)
-